2022
DOI: 10.1080/22221751.2022.2063073
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the transition of COVID-19 burden towards the young population while vaccines are rolled out in China*

Abstract: SARS-CoV-2 infection causes most cases of severe illness and fatality in older age groups. Over 92% of the Chinese population aged ≥12 years has been fully vaccinated against COVID-19 (albeit with vaccines developed against historical lineages). At the end of October 2021, the vaccination programme has been extended to children aged 3–11 years. Here, we aim to assess whether, in this vaccination landscape, the importation of Delta variant infections could shift COVID-19 burden from adults to children. We devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…However, our results suggested that susceptibility to the SARS-CoV-2 Omicron variant was greater in children and adolescents than in adults aged 18–29 years. The results might be related to the vaccination strategy at that time, which did not include children and adolescents; there is additional evidence that this vaccination strategy might increase SARS-CoV-2 infections in children and young adolescents 34. Our analysis of transmission capacity found that cases aged 0–4 years and 60 or more years had higher transmission capacity than adults.…”
Section: Discussionmentioning
confidence: 73%
“…However, our results suggested that susceptibility to the SARS-CoV-2 Omicron variant was greater in children and adolescents than in adults aged 18–29 years. The results might be related to the vaccination strategy at that time, which did not include children and adolescents; there is additional evidence that this vaccination strategy might increase SARS-CoV-2 infections in children and young adolescents 34. Our analysis of transmission capacity found that cases aged 0–4 years and 60 or more years had higher transmission capacity than adults.…”
Section: Discussionmentioning
confidence: 73%
“…Heterogeneous vaccine was indicated for high-income countries in two (0.5%) articles [ 106 , 382 ]. In 95 articles (23.1%), the difference in days between administered doses were considered; out of these, 22 articles (23.2%) considered a 21-day interval between doses [ 55 , 60 , 69 , 100 , 122 , 133 , 134 , 140 , 187 , 216 , 217 , 221 , 302 , 303 , 329 , 330 , 335 , 342 , 383 , 384 , 424 , 425 ], while 22 (23.2%) considered a period of 21- to 28-day interval [ 42 , 90 , 116 , 119 – 121 , 136 , 142 , 151 , 155 , 184 , 204 , 205 , 258 , 260 , 273 , 324 , 328 , 351 , 354 , 356 , 366 ]. Additionally, 11 (11.6%) articles considered a period equal to or greater than three months [ 203 , 211 , 222 , 269 , 300 , 314 , 317 , 333 , 334 , 350 , 361 ].…”
Section: Resultsmentioning
confidence: 99%
“…The age for the cases of Shanghai epidemic tended to be younger than those in the epidemic of Wuhan [ 27 , 28 ] and other localized outbreaks[ 38 ]. Cases infected with Omicron variant were found to be younger than cases infected with other variants [ 35 ], partly due to COVID-19 vaccination [ 13 ]. The overall SAR of the epidemic was estimated to be 24.17% (95% CI: 23.09% to 25.25%), which was consistent with previous studies [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the transmission rate and SAR in children and adolescents were lower, the transmissibility of them to other household members is not negligible. Extending vaccination to children aged 3–11 years would protect them from infection and reduce the transmission of this age group [ 13 ]. Cases with self-isolation at home could still infect susceptible people, such as their family members or neighbors [ 7 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation